Why dermatology patients are hospitalized? : a study from Pakistan - Raza, Naeem; Saleem, Junaid; Dar, Nasser Rashid; Malik, Naveed Akhter (2009)
In most countries, there are no specified protocols or guidelines for admitting dermatology patients and admission criteria depend on assessment and sometimes the whim of the dermatologist. Although the severity and extent of the disease are the commonest reasons for hospitalizing dermatology patients, sometimes other factors also operate to provide comfort to the patient. This study was carried out to determine the reasons for hospitalizing patients on dermatology beds in secondary care hospitals of Pakistan. A questionnaire comprising patients’ demographic data, diagnosis, specific reasons for hospitalization and length of hospital stay was sent to dermatologists of 10 secondary care hospitals in the country.
Bibliografija: 20 jed.
Keywords: Hospitalizacija -- Dermatologija -- Pacijenti; Pakistan